2019
DOI: 10.1021/jacs.9b06546
|View full text |Cite|
|
Sign up to set email alerts
|

Establishing a Thermodynamic Landscape for the Active Site of Mo-Dependent Nitrogenase

Abstract: Nitrogenase enzymes are the only biological catalysts able to convert N 2 to NH 3 . Molybdenum-dependent nitrogenase consists of two proteins and three metallocofactors that sequentially shuttle eight electrons between three distinct metallocofactors during the turnover of one molecule of N 2 . While the kinetics of isolated nitrogenase has been extensively studied, little is known about the thermodynamics of its cofactors under catalytically relevant conditions. Here, we employ a recently described pyrenemodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 64 publications
2
57
0
6
Order By: Relevance
“…In order to achieve this, a novel polymer functionalized with pyrene was employed. It is reported that these studies are able to achieve N 2 fixation independent of the Fe protein and ATP‐hydrolysis, representing a new prospect for N 2 fixation by nitrogenase . However, much work is required to fully exploit MoFe protein catalysis in this system.…”
Section: Recent Examples Of Enzymatic Electrochemistry For Small Molementioning
confidence: 99%
“…In order to achieve this, a novel polymer functionalized with pyrene was employed. It is reported that these studies are able to achieve N 2 fixation independent of the Fe protein and ATP‐hydrolysis, representing a new prospect for N 2 fixation by nitrogenase . However, much work is required to fully exploit MoFe protein catalysis in this system.…”
Section: Recent Examples Of Enzymatic Electrochemistry For Small Molementioning
confidence: 99%
“…Somit ist es negativer als das Formalpotential des P-Clusters (À0.48 V vs. SCE). [11] Daraus lässt sich schließen, dass durch die Differenz À und die maximale Stromdichte (J max ) wurden zu 342 AE 43 mm N 3 À bzw. À515 AE 49 mA cm À2 berechnet (Abbildung 4 b).…”
Section: Ergebnisse Und Diskussionunclassified
“…Dies erlaubte die Untersuchung der elektrochemischen Kinetik für jeden der Cofaktoren in der Nitrogenase unter biologisch relevanten Bedingungen. [11] Die Theorie elektronischer Tunnelprozesse legt nahe, dass der direkte Elektronentransfer die korrekte Ausrichtung zwischen Elektronendonor und Akzeptor innerhalb eines Abstands von 14 für ein effizientes Elektronentunneln erfordert, [12,13] wodurch der Elektronentransfer schneller als die enzymatische Reaktion erfolgen kann, was eine hohe Gesamtaktivität der modifizierten Elektrode gewährleistet. [11,14] Dementsprechend ist der gemessene bioelektrokatalytische Strom ausschließlich auf die Enzymmoleküle zurückzuführen, die als Protein-Monolage innerhalb der Elektronentunneldistanz immobilisiert sind.…”
Section: Introductionunclassified
See 2 more Smart Citations